A preliminary evaluation of the validity of binge‐eating disorder defining features in a community‐based sample. Issue 5 (26th November 2015) - Klein, Kelly M.; Forney, K. Jean; Keel, Pamela K.
ABSTRACT: Objective: Little empirical attention has been paid to the DSM‐5 definition of binge‐eating disorder (BED), particularly to the associated features of binge episodes. The present study sought to determine how the associated features and undue influence of weight/shape on self‐evaluation contribute to evidence of a clinically significant eating disorder. Method: Secondary analyses were conducted on data ( N = 80; 76.3% women, 76.3% Caucasian, ages 18–43) collected through an epidemiological study of eating patterns. Descriptive statistics were used to report the sample prevalence of the features, independently and in combination. Correlations and alpha reliability were employed to examine relationships among associated features, distress regarding bingeing, and clinical diagnosis. Regression models and receiver‐operating characteristic (ROC) curves were used to determine the utility of the features for explaining variance in distress. Results: Internal consistency reliability for indicators was low, and several features demonstrated low or nonsignificant associations with distress and diagnosis. Feeling disgusted/depressed/guilty was the only unique predictor of distress ( p = 0.001). For the ROC curves, three features was the best threshold for predicting distress. Discussion: Results support the need to refine the features to ensure better detection of clinically significant eating pathology for research inclusion and treatment of the illness. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:524–528).